Zmiana społeczna a zmiana w edukacji - Szymański, Mirosław (Pedagogika Społeczna Nova, 2021)
The article consists of two parts. In the first one, the author characterizes the social change in a tradi- tional, modern, and post-modern society. He points out the different nature of the former change and the modern-day change. He shows the cultural consequences of these differences for the individual and the society. In both dimensions, the effects are positive and negative. Against this background arises the question as to what changes in education are currently being caused by the rapid social change. The author contemplates this issue in the second part of the article. He wonders what kind of education is needed in times of the rapid social change in order to thoroughly prepare the youth to face the challenges of the future. It is a difficult task, because in a rapidly changing society, it is hard to predict what will happen in the future. Therefore, it is necessary to shape those qualities of the young generation that will allow it to solve new problems, unknown today. The author discusses those presented by Jérémy Lamri. They are: creativity, communication, critical thinking, cooperation. These competencies will be crucial in the 21st century.